2004
DOI: 10.22358/jafs/73883/2004
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of protozoal selenium in young goats

Abstract: A balance trial was conducted to determine the availability and utilization of protozoal-selenium (Se) for young goats. Protozoal-Se was prepared from rumen fl uid of a sheep supplemented with 0.4 mg inorganic Se (sodium selenite). A milk replacer diet without Se was supplemented with either 0.1 mg/kg diet of protozoal-Se or inorganic Se or no Se (control). The utilization coeffi cient of Se did not vary signifi cantly (P>0.05) between kids supplemented with protozoal-Se and selenite. Blood Se level was simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, SeHLan supplemented diets may inhibit the growth of rumen fungi of Mucoromycota and unidentified_Fungi. Previous research has also confirmed that rumen microbial population is capable of incorporating selenium into their cells and ruminal protozoa can influence animal selenium status 36 . Our previous study indicated that dietary supplementation of low (LSE) and medium (MSE) SeHLan could effectively increase the body weight, average daily gain, improve the nutrients utilization and food conversion ratio of Shaanbei white cashmere wether goats, while high SeHLan (HSE) is not beneficial for cashmere goat growth 11 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, SeHLan supplemented diets may inhibit the growth of rumen fungi of Mucoromycota and unidentified_Fungi. Previous research has also confirmed that rumen microbial population is capable of incorporating selenium into their cells and ruminal protozoa can influence animal selenium status 36 . Our previous study indicated that dietary supplementation of low (LSE) and medium (MSE) SeHLan could effectively increase the body weight, average daily gain, improve the nutrients utilization and food conversion ratio of Shaanbei white cashmere wether goats, while high SeHLan (HSE) is not beneficial for cashmere goat growth 11 .…”
Section: Discussionmentioning
confidence: 86%
“…Akbar et al 38 investigated that lactating Murrah buffaloes fed Se enriched diets had the significantly higher protozoan count. Fujihara et al 36 also reported that when a diet supplemented with 0.2 mg/kg Se in the form of selenite, rumen protozoa could capture 0.52 mg Se/kg of protozoan dry matter in sheep. As we all known, Se as a component of glutathione peroxidase (GSH-Px) can protect cell membranes from peroxide damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, SeHLan supplemented diets may inhibited the growth of rumen fungi of Mucoromycota and unidenti ed_Fungi. Previous research has also con rmed that rumen microbial population is capable of incorporating selenium in to their cells and ruminal protozoa can in uence animal selenium status 49 . Therefore, we can speculate that Ciliophora are mainly responsible for selenium utilization in the rumen eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 94%
“…Akbar et al 51 investigated that lactating Murrah buffaloes fed Se enriched diets had the signi cantly higher protozoan count. Fujihara et al 49 also reported that when a diet supplemented with 0.2 mg/kg Se in the form of selenite, rumen protozoa could capture 0.52 mg Se/kg of protozoan dry matter in sheep. As we all known, Se as a component of glutathione peroxidase (GSH-Px) can protect cell membranes from peroxide damage.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data show that the fate of dietary selenium in ruminants is influenced not only by the chemical form of selenium supplemented to feed, but also by diet composition, rumen microbiota profile and population, and the selenium status of animals (Koenig et al, 1997;van Ryssen and Schroeder, 2003). It has been shown that ruminal bacteria as well as protozoa are able to incorporate selenium from both inorganic and organic sources into their own proteins (Hidiroglou et al, 1968;Hidiroglou and Zarkadas, 1976;Hudmann and Glenn, 1984;Fujihara et al, 2004) and also into wall components of microbial cells (Koenig et al, 1997). There is evidence to indicate that the metabolism of selenium in the rumen is dependent on the prevalence of particular species of bacteria.…”
Section: Ruminantsmentioning
confidence: 99%